Placenta Percreta with Bladder Invasion - A Challenges of An Obstetrician: A Case Report - Begum, Shahana; Khandaker, Shafaat Shariqa (Journal of Chittagong Medical College Teachers' Association, 2023)
A 32 years lady, 3rd gravida, para 2, was referred into Chittagong Medical College Hospital on 16 October 2022 at her 38 weeks of pregnancy with antepartum haemorrhage due to central placenta praevia with previous history of two caesarean section. On admission patient present with profuse per vaginal bleeding. Decision was taken for caesarean hysterectomy due to Placenta Accreta Spectrum (PAS). During operation it was shown that whole placenta with amniotic membrane was protruded out through the disrupted scar with extensive vascularity along the anterior portion of the lower uterine segment and appear to extend upto and around the bladder. baby was delivered by breech extraction by the side of the placenta after opening of membrane, after delivery of the baby bilateral uterine artery was ligated then caesarean hysterectomy was done with successive clamping. Bladder was injured during mobilization and repaired. Peroperative blood loss wasaverage, replaced 4-unit PCV and plasma expander. operation time was 1 hour. After completion of operation recovery was smooth from general anaesthesia, Postoperatively patient was managed with broad spectrum antibiotics for seven days and bladder drainage with foleys catheter for 14 days. Her postoperative period was uneventful, and the patient was discharged with baby from hospital at 25th postoperative day. JCMCTA 2023 ; 34 (1) : 145-148